2020
DOI: 10.3892/or.2020.7807
|View full text |Cite
|
Sign up to set email alerts
|

Role of RASA1 in cancer: A review and update (Review)

Abstract: Ras p21 protein activator 1 (RASA1) is a regulator of Ras GDP and GTP and is involved in numerous physiological processes such as angiogenesis, cell proliferation, and apoptosis. As a result, RASA1 also contributes to pathological processes in vascular diseases and tumour formation. This review focuses on the role of RASA1 in multiple tumours types in the lung, intestines, liver, and breast. Furthermore, we discuss the potential mechanisms of RASA1 and its downstream effects through Ras/RAF/MEK/ERK or Ras/PI3K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 126 publications
0
35
1
1
Order By: Relevance
“…The RASA1 gene plays an important role in controlling the angiogenesis process [27] . Studies have shown that reducing the function of the RASA1 gene interferes with the regulation of the angiogenesis process and causes various cancers, such as breast cancer [16] , [28] . It has been shown that increasing RASA1 levels by suppressing miR-145 can reduce the progression of ovarian cancer [29] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The RASA1 gene plays an important role in controlling the angiogenesis process [27] . Studies have shown that reducing the function of the RASA1 gene interferes with the regulation of the angiogenesis process and causes various cancers, such as breast cancer [16] , [28] . It has been shown that increasing RASA1 levels by suppressing miR-145 can reduce the progression of ovarian cancer [29] .…”
Section: Discussionmentioning
confidence: 99%
“…RASA1 and NF1 proteins, which are RasGAPs (Ras-GTPase Activating Proteins), terminate the active Ras state by hydrolyzing GTP to GDP, thus negatively regulating the Ras pathway [15] . Accordingly, the development of various mutations and disruption of the expression of this tumor suppressor RasGAPs can lead to the formation of various types of cancers as well as endometriosis [16] , [17] .…”
Section: Introductionmentioning
confidence: 99%
“…Recent work has indicated the important involvement of RASA1 in capillary and arteriovenous malformations 36 . Moreover, RASA1 is capable of regulating neoplastic transformation and tumour progression 37 . In this article, RASA1 was identified as a direct and functional target of miR‐20a‐3p in modulating HaCaT keratinocyte migration.…”
Section: Discussionmentioning
confidence: 86%
“…36 Moreover, RASA1 is capable of regulating neoplastic transformation and tumour progression. 37 In this article, RASA1 was identified as a direct and functional target of miR-20a-3p in modulating HaCaT keratinocyte migration. Similarly, Shi et al ascertained that miR-31 enhanced keratinocyte migration and wound re-epithelialization phenotype via directly targeting RASA1.…”
Section: Discussionmentioning
confidence: 98%
“…SOD is an antioxidant enzyme that catalyzes the reactive oxygen species (ROS) into hydrogen peroxide and oxygen molecules to inhibit senescence and apoptosis ( Nguyen et al, 2020 ). RASA1 is a modulator of Ras GDP and GTP and plays an important role in several physiological processes such as angiogenesis, cell proliferation and apoptosis ( Zhang Y. et al, 2020 ). In addition, Lei et al observed that miR-132-3p expression was significantly up-regulated after femoral artery occlusion, and the hind limb perfusion recovery after ischemia was slower in knockout mice compared with wild-type mice ( Lei et al, 2015 ; Yue et al, 2018 ).…”
Section: Bone Microvascular Endothelial Cellsmentioning
confidence: 99%